2020
DOI: 10.1111/apa.15217
|View full text |Cite
|
Sign up to set email alerts
|

Difficult birth is the main contributor to birth‐related fracture and accidents to other neonatal fractures

Abstract: Aim Specific birth‐related fractures have been studied; underestimates might be a problem. We aimed to assess all fractures diagnosed as birth‐related as well as other neonatal fractures. Methods A population‐based study on all infants born in Sweden 1997‐2014; data were retrieved from the Swedish Health Registers (10th version of International Classification of Diseases. Outcome measures were birth‐related fractures (ICD‐10 P‐codes) and other neonatal fractures (ICD‐10 S‐codes). Results The overall fracture i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 24 publications
2
33
0
3
Order By: Relevance
“…Rib fractures may occur during birth [7]. We have previously shown that rib fractures diagnosed among neonates have an association with difficult birth [10]; the register case-control study supports this, as the controls were more often delivered by vacuum extraction and there was a higher proportion of big babies among controls. It is possible that there were birth-related rib fractures in the case-series, but this could not be ascertained.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Rib fractures may occur during birth [7]. We have previously shown that rib fractures diagnosed among neonates have an association with difficult birth [10]; the register case-control study supports this, as the controls were more often delivered by vacuum extraction and there was a higher proportion of big babies among controls. It is possible that there were birth-related rib fractures in the case-series, but this could not be ascertained.…”
Section: Discussionmentioning
confidence: 79%
“…The possible non-accidental trauma mechanism causing rib fractures has not been fully established [8], but the most common theory is thoracic compression when the infant is violently shaken [2]. Rib fractures, including multiple fractures, are rarely reported in association with birth, only in one case-series [9] and one population register study [10]. In both studies, the infants had concomitant clavicle fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosies of birth-related fractures might be delayed for femur fractures, [1,14] especially among the preterm-born, [15] and for humerus shaft fractures [3,8,11]. We have previously reported that some birth-related fractures of femur or other long bones are diagnosed after the rst week of life and in some cases at even higher age [6]. Our ndings show an overlap between birth-related femur fractures and other long bone fractures.…”
Section: Discussionmentioning
confidence: 63%
“…Our cases shared perinatal risk factors con rming the state of knowledge. For femur shaft fracture, these factors were breech presentation [1,2,6], multiple birth, and prematurity [1,6], and for humerus shaft fractures, they were vacuum-assisted delivery, shoulder dystocia, and heavy birth weight, as reported for other birth-related long bone fractures [6]. A high proportion of cesarean delivery in connection with shaft fractures [1][2][3] was not evident from our ndings.…”
Section: Discussionmentioning
confidence: 63%
“…However, although it is rare, skull fracture could occur at birth if there are difficulties during delivery. The overall fracture incidence was 2–3.7 per 100000 live births [ 12 , 17 ]. Some insists on that this data is underestimated because of undetected clinically silent simple linear fractures [ 3 , 17 , 25 ].…”
Section: Skull Fracturesmentioning
confidence: 99%